2022
DOI: 10.1007/s00406-022-01417-5
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated atrophy in dopaminergic targets and medial temporo-parietal regions precedes the onset of delusions in patients with Alzheimer’s disease

Abstract: People with Alzheimer’s disease (AD) and delusions have worse quality of life and prognosis. However, early markers of delusions have not been identified yet. The present study investigated whether there are any detectable differences in grey matter (GM) volume and cognitive changes in the year before symptom onset between patients with AD who did and did not develop delusions. Two matched samples of AD patients, 63 who did (PT-D) and 63 who did not develop delusions (PT-ND) over 1 year, were identified from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 94 publications
1
2
0
Order By: Relevance
“…Thus, the evidence presented, here, showing ventral striatum and the dorsal caudate de cits since the MCI-AD phase are important tools for early diagnosis. This is perfectly in line with previous works pinpointing dopaminergic de cits as predictive hallmarks of the pathology and of early conversion from MCI to AD-DEM [12,34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the evidence presented, here, showing ventral striatum and the dorsal caudate de cits since the MCI-AD phase are important tools for early diagnosis. This is perfectly in line with previous works pinpointing dopaminergic de cits as predictive hallmarks of the pathology and of early conversion from MCI to AD-DEM [12,34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Of note, these studies also confirmed that the extend of gray matter atrophy in mesocorticolimbic dopaminergic targets since the MCI stage was associated with greater severity of NPS, in particular depression linked to the meso-cortical route, anxiety linked to the mesolimbic route, and apathy linked to the mesohippocampal/meso-amygdaloid route ( 136 ). Indeed, stronger loss of gray matter in dopaminergic pathways was also paralleled by a worsening not only of episodic memory but also of behavioral alterations, related to the emergence of psychiatric symptoms and delusions in patients with AD ( 137 ). Given the link between the mesocorticolimbic dopamine and NPS, and the fact that these symptoms speed up the disease progression, it is not surprising that functional disconnection of the VTA with mesocorticolimbic targets can accelerate the conversion from the MCI stage to clinical AD ( 137 , 141 , 142 ).…”
Section: Dopamine In Alzheimer's Diseasementioning
confidence: 99%
“…Indeed, stronger loss of gray matter in dopaminergic pathways was also paralleled by a worsening not only of episodic memory but also of behavioral alterations, related to the emergence of psychiatric symptoms and delusions in patients with AD ( 137 ). Given the link between the mesocorticolimbic dopamine and NPS, and the fact that these symptoms speed up the disease progression, it is not surprising that functional disconnection of the VTA with mesocorticolimbic targets can accelerate the conversion from the MCI stage to clinical AD ( 137 , 141 , 142 ).…”
Section: Dopamine In Alzheimer's Diseasementioning
confidence: 99%